Tauroursodeoxycholic acid in patients with amyotrophic lateral sclerosis: The TUDCA-ALS trial protocol - Albanese, Alberto; Ludolph, Albert Christian; McDermott, Christopher J.; Corcia, Philippe; Van Damme, Philip; Van den Berg, Leonard H.; Hardiman, Orla; Rinaldi, Gilberto; Vanacore, Nicola; Dickie, Brian; , TUDCA-ALS Study Group; Tornese, Paolo; et al. (Frontiers in Neurology, 2022)
Background. Amyotrophic lateral sclerosis (ALS) is a chronic neurodegenerative rare disease that affects motor neurons in the brain, brainstem, and spinal cord, resulting in progressive weakness and atrophy of voluntary skeletal muscles. Although much has been achieved in understanding the disease pathogenesis, treatment options are limited and in Europe riluzole is the only approved drug. Recently some other drugs showed minor effects. Methods. The TUDCA-ALS trial is a phase III, multicentre, randomized, double-blind, placebo-controlled, parallel-group clinical trial. The study aims to enrol 320 patients in 25 centres across seven countries in Europe. Enrolled patients are randomized to one of two treatment arms: TUDCA or identical placebo by oral route. The study measures disease progression during the treatment period and compare it to natural progression during a no-treatment run-in phase. Clinical data and specific biomarkers are measured during the trial. The study is coordinated by a consortium composed of leading European ALS centres. Conclusion. This trial is aimed to determine whether TUDCA has a disease-modifying activity in ALS. Demonstration of TUDCA efficacy, combined with the validation of new biomarkers, could advance ALS patient care.